ELECTRICAL-PROPERTIES OF BETA-LIXV2O5 THIN-LAYERS PREPARED BY THE SOL-GEL PROCESS - BAE, SY; MIYAYAMA, M; YANAGIDA, H (AMER CERAMIC SOC, 1994)
The electrical properties of a highly oriented thin layer of lithium vanadium beta bronze, beta-LixV2O5, were investigated through dc and ac conductivity measurements. The ionic transference number was determined by a simplified polarization method employing ion-blocking electrodes. The electronic conductivity was 10(-3) to 10(-2) S.cm-1 in air or N2 at 300-400-degrees-C, which was lower than that of a randomly oriented sintered specimen. The ionic conductivity was 10(-2)-10(-1)s.cm-1 at 350-degrees-C, resulting in a high ion transference number of 0.8-0.9; it was higher than that reported for a bulk specimen. The lower electronic conductivity and higher ionic conductivity were assumed to be due to (1) the oriented microstructure, i.e., alignment of the b-axis along the substrate direction which enhanced Li+ conduction through tunnels along the b-axis, and (2) an open crystallographic structure, which promoted ionic motion in an open channel between adjacent (a-c) planes and suppressed the electron hopping process in the b-axis direction.
Keywords: VANADIUM-OXIDE BRONZES